Conductive fiber structure and bioelectrode

The conductive fiber structure, featuring synthetic fiber bundles and a proportionally optimized conductive resin distribution, addresses the issue of washing durability and conductivity loss in biological electrodes, achieving excellent durability and maintaining low surface resistivity after repeated washing.

JP7659147B2Active Publication Date: 2025-04-09AI SILK CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020164562
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-09
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

Existing conductive fiber structures for biological electrodes suffer from poor washing durability and conductivity loss due to the peeling off of conductive materials during repeated washing.

Method used

A conductive fiber structure with a substrate of synthetic fiber bundles and a conductive resin, where the fiber region and non-fiber region are specifically proportioned in the fiber bundle cross-section, and the conductive resin occupies a specific proportion in the non-fiber region, ensuring the resin is held within the fiber bundle.

Benefits of technology

The proposed structure significantly enhances washing durability by maintaining conductivity even after 100 washes, with surface resistivity remaining low, thus ensuring the electrode's performance over extended use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659147000002
    Figure 0007659147000002
  • Figure 0007659147000003
    Figure 0007659147000003
  • Figure 0007659147000004
    Figure 0007659147000004
Patent Text Reader

Abstract

To provide a conductive fiber structure capable of improving washing durability.SOLUTION: Provided is a conductive fiber structure including a base material composed of a fiber bundle that includes synthetic fibers, and a conductive resin present in the base material. The fiber bundle is composed of a fiber region where fibers exist and a non-fiber region where no fibers exist. The conductive fiber structure, inside the fiber bundle on a cut surface where the fiber bundle is cut in a direction orthogonal to a fiber longer direction, includes a non-fiber region where an area ratio of the fiber region / the non-fiber region in a circle with a diameter of 30 μm having four or more points of centroid on a single fiber cross section is 20 / 80 to 80 / 20, and an area ratio of the conductive resin in the non-fiber region is 40 to 90%. The conductive resin contains a conductive polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive fiber structure including a substrate constituted by a fiber bundle containing synthetic fibers and a conductive resin present in the substrate, and to a bioelectrode including the same as an electrode. [Background technology]

[0002] In recent years, many electrodes that can measure the heart rate and electrical biosignals of humans and animals using conductive fibers, as well as wearable sensors that use electrodes, have been developed. In addition, electrical muscle stimulation (EMS) applications that actively promote muscle movement by electrically stimulating the living body, especially the muscles, through electrodes are also being actively developed. These have the purpose of improving people's safety and health. Electrodes required for this purpose should be in planar contact with the living body surface and should be highly durable to washing. In addition, for EMS applications, the resistance value of the electrodes must be 1000Ω or less; if it exceeds 1000Ω, the electrodes will heat up and there is a risk of an accident.

[0003] Conventionally, as an electrode to be in planar contact with a biological surface, a conductor containing a conductive polymer such as PEDOT-PSS (poly 3,4-ethylenedioxythiophene-polystyrene sulfonate) has been impregnated into and / or attached to a base fiber to produce a conductive polymer fiber in which the conductor is in close contact with the base fiber, and a bioelectrode using this conductive polymer fiber has been developed (see Patent Document 1 (Patent Publication No. 5706539)).

[0004] In addition, as an electrode with improved washing durability, a conductive fiber structure has been developed in which a conductive resin containing a conductive polymer is supported in the gaps between the single fibers that constitute the fiber structure, and when a cross section of the fiber structure in the thickness direction is observed, the area ratio of the conductive resin present in a region 15 to 30 μm from the surface is 15% or more (see Patent Document 2 (International Publication WO 2017 / 183463)).

[0005] Furthermore, in recent years, a technology has been developed in which a conductive polymer, PEDOT-PTS (poly-3,4-ethylenedioxythiophene-p-toluenesulfonic acid), which has a higher conductivity than PEDOT-PSS, is applied to the surface of a substrate; the conductive polymer is uniformly attached while remaining amorphous, improving washing durability (see Patent Document 3 (Patent Publication No. 6476480)). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5706539 [Patent Document 2] International Publication No. 2017 / 183463 Brochure [Patent Document 3] Patent No. 6476480 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Document 1, conductive polymer fibers with a large amount of conductor attached to the fiber surface are used, and the electrode formed into a textile shape by processing such conductive polymer fibers does not have high washing durability and is insufficient. In addition, in Patent Document 1, only silk fibers are actually used as the base fiber, and the structure is such that the conductor containing the conductive polymer is in close contact with the base fiber, but when synthetic fibers are used in particular, the conductor is difficult to be in close contact because it is incompatible with the conductive polymer and has poor adhesion. In addition, even if the conductor is in close contact immediately after production, the conductor peels off and falls off during washing, and the conductivity drops rapidly, making it insufficient.

[0008] The conductive fiber structure disclosed in Patent Document 2 has an area ratio of conductive resin present in a region 15 to 30 μm from the surface layer of 15% or more when the cross section in the thickness direction is observed. This document describes that the conductive resin is supported in the gaps between fibers, and that flexibility and washing durability are obtained by impregnating the conductive resin deep inside. The region 15 to 30 μm from the surface layer in the thickness direction varies depending on the thickness of the conductive fiber structure and the fiber diameter of the fibers constituting the conductive fiber structure, and therefore does not necessarily represent the deep part. Furthermore, even if the conductive resin is supported inside the fiber structure, there are cases in which washing durability is insufficient.

[0009] In the examples of Patent Document 2, the conductive resin is applied to the fibers by fine particles having a dispersed particle diameter of 200 nm or less, and the conductive resin is supported between the fibers, i.e., bonded, so that the conductivity is maintained even after 30 washes. However, in such an embodiment, the conductive resin is only supported between the fibers by incompatible conductive resin, so that the performance cannot be maintained for a practical number of washes. That is, when a conductive fiber structure containing a conductive resin is washed, the conductive material falls off from the surface layer in sequence due to frictional resistance with the washing machine and impact force between the laundry. When the washing is further repeated, after the conductive material supported on the fiber surface falls off, the conductive material falls off from the outer layer of the fiber in sequence toward the inner layer. Therefore, even if the method of supporting, i.e., bonding, a conductive polymer on a fiber has conductivity up to 30 washes, the conductive material falls off and the conductivity cannot be exhibited under harsh conditions of 100 washes, which is considered to be practical for about one year if washing is performed once every three days.

[0010] Although Patent Document 3 describes that the conductive polymer can be uniformly adhered, it is intended for adhesion to the surface of a substrate. In particular, when synthetic fibers are used as the substrate, the molecular structure and lack of hydrophilicity of the synthetic fibers make them incompatible with the conductive polymer, making it difficult to make the conductive polymer extend to the inside of the fiber bundles, leaving room for improvement in terms of washing durability.

[0011] In addition, in Patent Documents 2 and 3, the washing durability was evaluated by washing only about 30 times and 10 times, and it could not be said that the evaluation took practicality into consideration. The clothing described in Patent Documents 2 and 3 must come into contact with human skin. That is, to operate as a sensor, it is necessary to measure the electrocardiogram, and also to provide massage and muscle stimulation by electricity, if there is other clothing between the conductive fiber structure, electricity will not flow and the performance cannot be achieved. In this way, clothing that comes into contact with human skin is generally washed repeatedly due to problems such as odor caused by sweat. Although the frequency of wearing varies depending on the wearing scene, considering the use for one year, washing 30 times means wearing it once every 12 days, which is not very practical. Washing 100 times means wearing it once every 3 to 4 days, which is a level that can be said to be practical.

[0012] The present invention has been made in light of the above problems, and an object of the present invention is to provide a conductive fiber structure and a bioelectrode that can improve washing durability. [Means for solving the problem]

[0013] As a result of intensive research to achieve the above-mentioned object, the inventors of the present invention discovered that a conductive fiber structure comprising a substrate composed of a fiber bundle containing synthetic fibers and a conductive resin present within the substrate, wherein fiber regions and non-fiber regions are present in specific areas in the cross section of the fiber bundle and the area of ​​the non-fiber region occupied by the conductive resin is a specific ratio, has excellent washing durability because the conductive resin can be retained inside the fiber bundle, leading to the completion of the present invention.

[0014] That is, the present invention can be configured in the following manner. [Aspect 1] A conductive fiber structure comprising a substrate made of a fiber bundle containing synthetic fibers and a conductive resin present in the substrate, The fiber bundle is composed of a fiber region where fibers are present and a non-fiber region where fibers are not present, A conductive fiber structure comprising a fiber bundle on a cross section obtained by cutting the fiber bundle in a direction perpendicular to the longitudinal direction of the fibers, the fiber bundle having an area ratio of fiber region to non-fiber region within a circle of 30 μm in diameter containing four or more centers of gravity of single fiber cross sections of 20 / 80 to 80 / 20 (preferably 30 / 70 to 75 / 25, more preferably 40 / 60 to 65 / 35), and a non-fiber region having an area ratio of 40 to 90% (preferably 45 to 80%, more preferably 50 to 75%) of the non-fiber region occupied by a conductive resin, and the conductive resin comprises a conductive polymer. [Aspect 2] 2. The conductive fiber structure according to claim 1, wherein the conductive resin is present between the separated single fibers in the form of a sponge and / or a boundary film having interconnected pores. [Aspect 3] 3. The conductive fiber structure according to claim 1 or 2, wherein the synthetic fibers constituting the substrate have a non-circular cross section having three or more recesses. Aspect 4 The conductive fiber structure according to any one of aspects 1 to 3, wherein the base material comprises synthetic fibers having a single fiber fineness of 0.5 to 4 dtex (preferably 0.7 to 3 dtex, more preferably 1.0 to 2.5 dtex). Aspect 5 A conductive fiber structure according to any one of aspects 1 to 4, having a surface resistivity of 200 Ω / □ or less (preferably 150 Ω / □ or less, more preferably 100 Ω / □ or less) after 100 washings. Aspect 6 A bioelectrode comprising the conductive fiber structure according to any one of the first to fifth aspects as an electrode. Effect of the Invention

[0015] According to the conductive fiber structure of the present invention, the conductive resin can be retained within the fiber bundles even after more washings than before, taking into consideration actual wear, and the conductive fiber structure has excellent washing durability. [Brief description of the drawings]

[0016] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are merely for illustration and explanation, and should not be used to define the scope of the present invention, which is defined by the appended claims. [Figure 1] 1 is an enlarged photograph (magnification: 800 times) showing a cross section of the conductive fiber structure obtained in Example 1. [Diagram 2] 2 is an enlarged photograph (magnification: 800 times) showing a cross section of the conductive fiber structure obtained in Example 2. [Diagram 3] 1 is an enlarged photograph (magnification: 1000 times) showing a cross section of the conductive fiber structure obtained in Example 3. [Figure 4] FIG. 2 is a schematic cross-sectional view showing an example of a fiber cross-sectional shape having a irregular cross section having three or more recesses. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] [Conductive fiber structures] The conductive fiber structure of the present invention includes a substrate composed of a fiber bundle containing synthetic fibers, and a conductive resin present in the substrate. The fiber bundle refers to a bundle formed by combining two or more single fibers, and includes untwisted multifilament raw yarn immediately after spinning, and raw yarn that has been processed by twisting, false twisting, interlacing, etc. The conductive resin needs to be present in at least a part of the substrate, and the below-mentioned area ratio and area proportion ranges need to be satisfied at least in the part where the conductive resin is present.

[0018] The conductive fiber structure of the present invention is composed of a fiber region where fibers are present and a non-fiber region where no fibers are present on a cross section obtained by cutting a fiber bundle in a direction perpendicular to the fiber longitudinal direction. The fiber region refers to the region of the fibers themselves that constitute the fiber bundle. The non-fiber region refers to a region where something other than fibers is present, that is, a region where an air layer, conductive resin, etc. are present, and may be, for example, a region where an air layer exists between single fibers, or a region where a conductive resin exists between single fibers or on the fiber surface. The air layer refers to a region where no material such as fibers or conductive resin exists, and is a void.

[0019] In the conductive fiber structure of the present invention, the area ratio of the fiber region / non-fiber region in a circle of 30 μm diameter containing four or more centroids of the cross section of the single fiber is 20 / 80 to 80 / 20 in a cross section obtained by cutting the fiber bundle in a direction perpendicular to the fiber longitudinal direction. In the present invention, the circle of 30 μm diameter containing four or more centroids of the cross section of the single fiber refers to a portion determined by a method described below, and refers to a portion corresponding to the inside of the fiber bundle. By setting the area ratio of the fiber region to the non-fiber region in a specific range in the inside of the fiber bundle and widening the distance between the single fibers to a certain extent, it is possible to secure a space in which an air layer and a conductive resin can exist inside the fiber bundle, and the conductive resin can be held in the fiber bundle, thereby improving the washing durability. The area ratio of the fiber region / non-fiber region in a circle of 30 μm diameter containing four or more centroids of the cross section of the single fiber may be preferably 30 / 70 to 75 / 25, more preferably 40 / 60 to 65 / 35.

[0020] In the conductive fiber structure of the present invention, in a cross section obtained by cutting a fiber bundle in a direction perpendicular to the longitudinal direction of the fibers, within a circle having a diameter of 30 μm and containing four or more centers of gravity of single fiber cross sections, the proportion (area) of the conductive resin in the non-fiber region is 40 to 90%. By setting the area proportion of the conductive resin in the non-fiber region within a specific range and by having a specific amount of conductive resin that can be retained within the fiber bundle, conductivity can be maintained, thereby improving washing durability. Within a circle having a diameter of 30 μm and containing four or more centers of gravity of single fiber cross sections, the proportion (area) of the conductive resin in the non-fiber region may be preferably 45 to 80%, more preferably 50 to 75%.

[0021] In the conductive fiber structure of the present invention, the conductive resin may be present at least on the inside of the fiber bundle, and may further be adhered to the outer surface of the fiber bundle. In the conductive fiber structure of the present invention, the conductive resin may be adhered to the synthetic fibers on the inside and / or outside of the fiber bundle, but there may be some areas where the conductive resin is not adhered. Even if the adhesiveness between the conductive resin and the synthetic fibers is low, the conductive resin present on the outside of the fiber bundle will fall off during washing, but by confining the conductive resin inside the fiber bundle, it is possible to prevent the conductive resin from falling off during washing.

[0022] In the present invention, the area ratio of the fiber region / non-fiber region and the area ratio of the conductive resin in the non-fiber region are determined by the following method. The center of gravity is determined by image analysis of a cross-sectional photograph (SEM) of the conductive fiber structure, but it is necessary to distinguish between the synthetic fiber, the conductive resin, and the air layer first. In addition, if other materials are present, it is necessary to distinguish those materials as well. For example, it is preferable to treat the conductive fiber structure with osmium as a pretreatment to clarify the boundary surface, and since osmium adsorbs to the conductive polymer but not to the synthetic fiber, it is possible to clarify the boundary surface. After distinguishing the boundary between the synthetic fiber, the conductive resin, and the air layer using image analysis software, the center of gravity of the single fiber cross section of the synthetic fiber is specified using the analysis software, and its position is plotted on the cross-sectional photograph. Then, the center of gravity of four single fiber cross sections is selected, a circle with a diameter of 30 μm is drawn with the center of gravity of the four points as the center, and a part where four or more centers of gravity of the single fiber cross sections are included in the circle is found, and the area ratio of the fiber region / non-fiber region and the area ratio of the conductive resin in the non-fiber region of the part can be calculated using image analysis software. When the base material is composed of multiple types of fiber bundles in a woven or knitted structure, it is sufficient that at least one type of fiber bundle satisfies the above-mentioned specific area ratio and area proportion.

[0023] Furthermore, in the conductive fiber structure of the present invention, in a cross section obtained by cutting a fiber bundle in a direction perpendicular to the longitudinal direction of the fibers, a specific proportion of air layers are present inside the fiber bundle as non-fiber regions, and the air layers act as a cushion against shocks during washing, improving washing durability and providing excellent flexibility. In the non-fiber regions within a circle with a diameter of 30 μm that contains four or more centers of gravity of single fiber cross sections, the area ratio of conductive resin / air layers may be 40 / 60 to 90 / 10, preferably 45 / 55 to 80 / 20, and more preferably 50 / 50 to 75 / 25.

[0024] The conductive resin may be present in a sponge-like and / or boundary film-like form between the separated single fibers. The term "sponge-like" refers to a form in which the conductive resin present between the single fibers is porous and contains an air layer (void). The term "boundary film-like" refers to a form in which the conductive resin has a film-like structure formed by the surface tension acting between adjacent single fibers when the conductive resin dries during the manufacture of the conductive fiber structure. The term "conductive resin is present in a sponge-like and boundary film-like form" means that a part in which the conductive resin is present in a sponge-like form and a part in which the conductive resin is present in a boundary film-like form may be mixed in one fiber bundle in the conductive fiber structure, or a fiber bundle in which the conductive resin is present in a sponge-like form and a fiber bundle in which the conductive resin is present in a boundary film-like form may be mixed among multiple fiber bundles in the conductive fiber structure. By having a form in which the conductive resin is not filled between adjacent single fibers but contains voids between the single fibers, it is possible to improve washing durability and provide excellent flexibility.

[0025] The conductive fiber structure of the present invention can have a basis weight that can be appropriately determined depending on the application. The basis weight is not particularly limited, but is, for example, 50 to 300 g / m 2 It may be to some extent.

[0026] The conductive fiber structure of the present invention may have a surface resistivity of 200 Ω / □ or less after 100 washes, preferably 150 Ω / □ or less, and more preferably 100 Ω / □ or less. The lower limit of the surface resistivity after 100 washes may be, for example, 0.1 Ω / □ or more. It is also preferable that the surface resistivity is within the above range even after 200 washes. The surface resistivity after 100 washes is a value measured by the method described in the Examples below.

[0027] (base material) The substrate is not particularly limited as long as it is made of fiber bundles containing synthetic fibers. Examples of the substrate include fabrics such as woven fabrics, knitted fabrics, and nonwoven fabrics, and preferably woven fabrics and knitted fabrics. The present invention makes it possible to maintain electrical conductivity even when an elastic woven fabric or knitted fabric is used as a substrate, which has been difficult to maintain electrical conductivity in the past. That is, it has been very difficult to use a highly stretchable knitted fabric as a substrate among conventional conductive fiber structures. The fiber bundles forming the loops of the knitted fabric are normally under relatively low tension and are arranged to spread in the lateral direction of the fiber axis, but when the knitted fabric is pulled, tension is applied to the loops, and the fiber bundles are stretched, resulting in deformation of the structure. This deformation of the structure promotes peeling of the fiber bundles and the conductive resin, ultimately causing a large amount of the conductive resin to fall off and losing electrical conductivity, making it difficult to use a knitted fabric as a substrate for a conductive fiber structure. On the other hand, the conductive fiber structure of the present invention has a structure in which the conductive resin is present inside the fiber bundles, so that the conductive resin does not fall off even when the knitted loops are deformed, and the conductive resin can maintain conductivity even in highly stretchable knitted fabrics. For the same reasons as above, the conductive fiber structure can also maintain conductivity in highly stretchable woven fabrics using polyurethane elastic yarns, side-by-side type highly crimped yarns, etc.

[0028] Synthetic fibers are fibers formed using fiber-forming synthetic polymers, and may be formed from one type of synthetic polymer, or may be formed from two or more types of synthetic polymers. Examples of synthetic fibers include polyolefin fibers formed from polyolefin resins such as polyethylene and polypropylene; polyester fibers formed from polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and polylactic acid; polyamide fibers formed from polyamide resins such as polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, and polyamide 612; polyurethane fibers formed from polyurethane resins; acrylic fibers and acrylic fibers formed from polyacrylonitrile; and acrylate fibers formed from acrylate resins such as polyacrylic acid and polymethacrylic acid. These fibers may be used alone or in combination of two or more. Of these fibers, polyester fibers, polyamide fibers, and polyurethane fibers are preferably used. The conductive fiber structure of the present invention has excellent washing durability even when a synthetic fiber that is not compatible with a conductive polymer is used as the substrate, since the synthetic fiber can be present inside the fiber bundle. For example, the ratio of synthetic fibers to the fibers constituting the substrate may be 50% by mass or more, preferably 60% by mass or more, and more preferably 70% by mass or more. The upper limit of the ratio of synthetic fibers is not particularly limited, but may be 100% by mass. The fibers constituting the substrate may contain various natural fibers and semi-synthetic fibers in addition to synthetic fibers. For example, natural fibers such as cotton, hemp, wool, and pulp; regenerated fibers such as rayon, polynosic, and cupra; and semi-synthetic fibers such as acetate and triacetate.

[0029] The synthetic fibers constituting the substrate may be non-composite fibers or composite fibers (such as core-sheath composite fibers, islands-in-the-sea composite fibers, and side-by-side composite fibers). The cross-sectional shape of the synthetic fibers is not particularly limited, and may be a round cross-section, a flat cross-section other than a round cross-section, a hollow cross-section, or other irregular cross-sections. From the viewpoint of expanding the space between the single fibers, it is preferable that the synthetic fibers contain fibers in the fiber bundle that have an irregular cross-section shape having three or more (for example, 3 to 6) recesses. The recesses refer to portions that have a recessed portion toward the inside of the fiber on the outer periphery of the cross-section of the single fiber. When the fibers having such an irregular cross-sectional shape are contained, even if the single fibers are close to each other, the recesses create spaces between the single fibers, so that the liquid containing the conductive resin can be permeated by capillary action and a large amount of the conductive resin can be incorporated. In addition, synthetic fibers include synthetic fibers with a straight shape that does not have crimp and false twisted yarns that have been crimped. Either form is acceptable, but it is preferable to have a crimped shape that has been false twisted in order to more strongly exhibit capillary action. In particular, false twisting of fibers with irregular cross sections having three or more recesses is more preferable because some of the recesses are deformed into a cylindrical shape, making it more difficult to release the absorbed liquid than fibers with a straight shape. Examples of irregular cross sections with three or more recesses in the cross section include a multi-lobed or star-shaped (e.g., 3 to 6-lobed) shape as shown in FIG. 4. Preferably, the fibers may include irregular cross sections with four or more recesses in the cross section. The fiber bundle may contain fibers of one or more types of cross-sectional shapes. For example, the ratio of the total fineness of fibers having a modified cross section with three or more recesses to the total fineness of all fibers in the fiber bundle may be 50% or more, preferably 60% or more, and more preferably 70% or more. There is no particular upper limit to this, but it may be 100%.

[0030] The single fiber fineness of the synthetic fibers constituting the substrate may be 0.5 to 4 dtex. By using synthetic fibers having a single fiber fineness in this range, it is possible to secure a space between the single fibers and improve the flexibility of the conductive fiber structure. The single fiber fineness of the synthetic fibers constituting the substrate may be preferably 0.7 to 3 dtex, more preferably 1.0 to 2.5 dtex. The synthetic fibers having the above single fiber fineness may be contained in 40 mass% or more, preferably 50 mass% or more of the fibers constituting the substrate. The upper limit of the proportion of the synthetic fibers having the above single fiber fineness among the fibers constituting the substrate is not particularly limited, but may be 100 mass%. The single fiber fineness is a value measured by the method described in the examples described later.

[0031] The number of single fibers constituting the fiber bundle may be adjusted depending on the application, and may be, for example, 10 to 500, preferably 20 to 200, and more preferably 30 to 100. The fineness of one fiber bundle may be, for example, 20 to 500 dtex, preferably 30 to 200 dtex, and more preferably 35 to 110 dtex.

[0032] (Conductive resin) The conductive resin includes a conductive polymer. The conductive polymer is a polymer having electrical conductivity. The conductive polymer is not particularly limited as long as it can impart electrical conductivity to the conductive fiber structure, and a known conductive polymer can be used. For example, polythiophene, polypyrrole, polyaniline, poly(p-phenylene sulfide), polyacetylene, poly(p-phenylene vinylene), polynaphthalene, and derivatives thereof can be mentioned, and a complex of these with a dopant is preferably used. These conductive polymers may be used alone or in combination of two or more. Among these conductive polymers, water-soluble conductive polymers (for example, polythiophene, polypyrrole, polyaniline, poly(p-phenylene sulfide), and derivatives thereof) are preferred, and from the viewpoint of having high electrical conductivity, a polymer having a thiophene derivative as a monomer component is preferred, and a complex of a polymer having a thiophene derivative as a monomer component and a dopant is more preferred.

[0033] As a polymer having a thiophene derivative as a monomer component, poly(3,4-disubstituted thiophene) is preferable. Among poly(3,4-disubstituted thiophene), poly(3,4-diC 1-4 alkoxythiophene) or poly(3,4-C 1-4 Alkylenedioxythiophene) is preferred, and specifically, poly(3,4-ethylenedioxythiophene) [PEDOT] or a derivative thereof is more preferably used.

[0034] Examples of the dopant include halogens, inorganic acids or salts thereof, low molecular weight sulfonic acids or salts thereof, low molecular weight carboxylic acids or salts thereof, sulfonic acid polymers (e.g., polystyrene sulfonic acid [PSS], polyvinyl sulfonic acid, polyisoprene sulfonic acid, etc.), and carboxylic acid polymers (e.g., polyacrylic acid, polymethacrylic acid, polymaleic acid, etc.). These dopants may be used alone or in combination of two or more. From the viewpoint of imparting high conductivity, low molecular weight sulfonic acids or salts thereof, low molecular weight carboxylic acids or salts thereof, or sulfonic acid polymers are preferably used as dopants to be used as a complex with a polymer having a thiophene derivative as a monomer component. 1-12 Alkyl sulfonic acid, benzene sulfonic acid, toluene sulfonic acid, Perfluoro C 1-12 Examples of the low molecular carboxylic acid include trifluoroacetic acid, salicylic acid, etc., and examples of the sulfonic acid polymers include polystyrene sulfonic acid, polyvinyl sulfonic acid, etc. Specifically, the dopant used as a complex with poly(3,4-ethylenedioxythiophene) is preferably p-toluenesulfonic acid [pTS] or its iron salt, trifluoroacetic acid or its salt, or polystyrenesulfonic acid, and more preferably p-toluenesulfonic acid or its iron salt from the viewpoint of imparting higher electrical conductivity.

[0035] The conductive resin may contain other substances than the conductive polymer, for example, an oxidizing agent. The oxidizing agent is an additive used in a polymerization reaction to synthesize a conductive polymer, and examples thereof include iron salts of inorganic acids such as ferric chloride, ferric sulfate, and ferric nitrate; copper salts of inorganic acids such as cupric chloride and cupric sulfate; persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate; periodates such as potassium periodate; iron salts of organic acids such as iron salts of p-toluenesulfonic acid; aluminum chloride, nitrosonium tetrafluoroborate, boron trifluoride, bromine, and iodine. These oxidizing agents may be used alone or in combination of two or more.

[0036] The conductive resin has high conductivity, for example, 1×10 -2 The conductive resin may have an electrical conductivity of 1000 S / cm or more, preferably 0.3 S / cm or more, and more preferably 1.0 S / cm or more. The upper limit of the electrical conductivity of the conductive resin may be, for example, 1000 S / cm.

[0037] [Method of manufacturing conductive fiber structure] The method for producing a conductive fiber structure of the present invention may include at least a coating step of coating a conductive resin-forming solution onto a substrate composed of a fiber bundle containing synthetic fibers, a penetration step of penetrating the conductive resin-forming solution into the fiber bundle of the substrate, and a polymerization step of polymerizing the conductive resin-forming solution that has penetrated the substrate to synthesize a conductive polymer.

[0038] In the coating step, the conductive resin forming solution may be applied to the substrate by a known coating method such as a dipping method, a coating method, a spraying method, etc. From the viewpoint of impregnating the substrate with the conductive resin forming solution and synthesizing a conductive polymer inside the substrate, the coating method, the spraying method, etc. are preferred. The conductive resin forming solution may be applied to the entire surface or a part of the substrate depending on the purpose.

[0039] In the coating step, tension may not be applied to the substrate from the viewpoint of increasing the permeability of the conductive resin-forming solution. By not applying tension to the substrate, a space that allows a large amount of conductive resin to be incorporated in the fiber bundle can be generated. The method of coating the conductive resin-forming solution without applying tension to the substrate may be a method of coating the conductive resin-forming solution in a state where the substrate is placed stationary on a predetermined base, and may be, for example, a batch method or a continuous method using a belt conveyor or the like.

[0040] The conductive resin forming solution is a solution containing a component capable of forming a conductive polymer, and may contain a monomer of the conductive polymer. From the viewpoint of making it easier to penetrate the conductive resin forming solution into the fiber bundle in the subsequent penetration step, it is preferable to use a solution containing a monomer constituting the conductive polymer. The conductive resin forming solution may contain a thiophene derivative as a monomer, and may preferably contain a monomer of poly(3,4-ethylenedioxythiophene) (e.g., 3,4-ethylenedioxythiophene).

[0041] When a solution containing a monomer of a conductive polymer is used as the conductive resin forming solution, it may contain a component that contributes to the polymerization of the monomer, such as an oxidizing agent, a catalyst, or a polymerization initiator. For example, when the monomer is a thiophene derivative, a polymer containing the thiophene derivative as a monomer component can be obtained by oxidative polymerization using an oxidizing agent, and may contain the above-mentioned oxidizing agent, preferably an iron salt of an inorganic acid or an iron salt of an organic acid. In addition, when an iron salt of a low molecular weight sulfonic acid or an iron salt of a low molecular weight carboxylic acid is contained, it can function as an oxidizing agent and also as a dopant. Preferably, an iron salt of p-toluenesulfonic acid is used, so that it can function as both an oxidizing agent and a dopant.

[0042] The solvent used in the conductive resin forming solution is not particularly limited as long as it can dissolve the components capable of forming a conductive polymer, and examples thereof include water; alcohols such as methanol, ethanol, 2-propanol, 1-propanol, and glycerin; ethylene glycols such as ethylene glycol, diethylene glycol, and triethylene glycol; propylene glycols such as propylene glycol, dipropylene glycol, and tripropylene glycol; tetrahydrofuran; acetone; and acetonitrile. These solvents may be used alone or in combination of two or more. Preferably, at least one solvent selected from the group consisting of water, alcohols, ethylene glycols, and acetonitrile may be used.

[0043] When a solution containing a monomer of a conductive polymer is used as the conductive resin forming solution, it is preferable to use ethanol as a solvent. When the conductive resin forming solution containing ethanol as a solvent is applied to a substrate to polymerize the monomer of the conductive polymer in the substrate, it becomes possible to remove the solvent at a relatively low temperature.

[0044] The conductive resin forming solution may contain various additives in addition to the components capable of forming a conductive polymer.

[0045] In the method for producing a conductive fiber structure of the present invention, it is preferable to apply the conductive resin forming solution three or more times as described below, and it is preferable that the amount of conductive resin forming solution applied each time is the maximum amount that ensures an amount that penetrates into the substrate while preventing droplets from falling from the substrate.

[0046] In the permeation step, the conductive resin-forming solution can be permeated into the fiber bundle. In the permeation step, the conductive resin-forming solution can be permeated into the fiber bundle of the substrate, and is not particularly limited as long as the conductive resin-forming solution can be permeated into the substrate by a known method such as pressing, roll pressing, or belt pressing.

[0047] In the polymerization step, polymerization may be carried out in the conductive resin-forming solution that has permeated the substrate to synthesize a conductive polymer. In the polymerization step, heating may be carried out from the viewpoint of promoting the polymerization reaction of the monomers of the conductive polymer, or in the case of a polymerization system that proceeds at room temperature, the reaction may be carried out at room temperature without heating from the viewpoint of controlling the polymerization reaction. For example, when 3,4-ethylenedioxythiophene and an oxidizing agent are mixed, it is preferable to carry out the polymerization reaction at room temperature.

[0048] In the method for producing a conductive fiber structure of the present invention, it is further preferable to apply the conductive resin forming solution again to the substrate to which the conductive resin has been applied, and from the viewpoint of satisfying a specific fiber region / non-fibrous region area ratio and a specific area ratio of the conductive resin in the non-fibrous region, it is preferable to carry out the application step and the penetration step three or more times. The steps from applying the conductive resin forming solution to the substrate to obtaining a substrate to which the conductive resin has been applied (including at least the application step and the penetration step, and optionally including the polymerization step) may be carried out three to five times.

[0049] Furthermore, by forming the conductive resin in several steps rather than all at once, the conductive resin can be made to have a sponge-like and / or boundary film-like structure inside the fiber bundle. That is, a conductive fiber structure containing a conductive resin can be obtained by performing the coating step and the penetration step at least three times, but by performing the coating step and the penetration step again on a conductive fiber structure that has been subjected to the coating step and the penetration step once, the conductive resin that was previously present and the conductive resin in the reapplied conductive resin-forming solution are bonded to each other, and a sponge-like or boundary film-like structure with communicating holes that is bonded to or peeled off from the substrate can be formed, which is preferable from the viewpoint of forming an air layer inside the fiber bundle.

[0050] [Bioelectrode] The conductive fiber structure of the present invention can be used for a bioelectrode that is in direct contact with a living body and can acquire and / or impart an electric signal. The conductive fiber structure of the present invention is used as an electrode member, and its shape and size are not particularly limited as long as it can be in planar contact with the surface of a living body.

[0051] In the bioelectrode of the present invention, a resin layer may be laminated on the conductive fiber structure as an electrical insulating layer. The resin layer may be in the form of a fabric such as a woven fabric, knitted fabric, or nonwoven fabric, or may be in the form of a film, sheet, or the like.

[0052] The bioelectrode of the present invention may be a bioelectrode that detects electrical signals from a living body, such as a heartbeat, or a bioelectrode that applies electrical stimulation to a living body, such as electrical muscle stimulation (EMS). The bioelectrode of the present invention is not particularly limited as long as the conductive fiber structure used has a fit to the living body and is in direct contact with the living body. In addition to pads, gloves, belts, etc., the bioelectrode may be at least a part of various clothing items such as underwear (shirts, blouses, T-shirts, tank tops, camisoles, spaghetti strap shirts, tube tops, halter tops, brassieres, trousers, pants, girdles, socks, tights, stockings, singlets, leotards, swimsuits, wetsuits, etc.), footwear (leather shoes, sneakers, boots, sandals, pumps, mules, slippers, etc.), headbands, wristbands, neck wraps, belly wraps, suspenders, gloves, watches, hats, supporters, bandages, etc., because of its excellent washing durability. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, various physical properties were measured by the following methods.

[0054] [Single fiber size] The total fineness of the fiber bundle constituting the substrate was measured according to JIS L 1013 "Testing method for chemical fiber filament yarn". The total fineness was then divided by the number of filaments constituting the fiber bundle to obtain the single fiber fineness.

[0055] [Metaku] According to JIS L 1096 "Testing method for woven and knitted fabrics" 8.3, the basis weight (g / m 2 ) was measured.

[0056] [Area ratio, area proportion] First, the conductive fiber structure is cut with a razor to prepare an observation sample with an exposed cross section of the fabric. The sample is then subjected to a gas phase dyeing process using osmium tetroxide at room temperature (23°C) to electronically dye the sample and provide it for microscopic observation. The cross section of the osmium-treated conductive fiber structure was imaged using a scanning electron microscope (SEM) (Hitachi High-Technologies Corporation, "SU-70") at 23°C, high vacuum, and 800x magnification. The obtained images were segmented using the image analysis software "Avizo for EM systems software" manufactured by Thermo Fisher Scientific to separate the fiber region from the non-fiber region. In addition, in the non-fiber region, the air layer region and the conductive resin region were separated by the same segmentation. In addition, the center of gravity of each single fiber cross section was determined by the image analysis software. Then, four points were selected from the centers of gravity determined by the image analysis software, and a circle with a diameter of 30 μm was drawn with the center of the four centers of gravity as the center. If four or more centers of gravity of the single fiber cross section were included in the circle, the circle was determined as the target region. In the region, the fiber region and the non-fiber region were separated by the above segmentation, and further, the air layer region and the conductive resin region were separated in the non-fiber region, and the area of ​​each was calculated, and the area ratio of each was obtained. The above region determination and area ratio calculation were counted as one measurement point. Similarly, measurements were taken at least three times within another circle with a diameter of 30 μm that contained four or more centers of gravity, and the average values ​​were calculated to determine the area ratio of the fiber region to the non-fiber region and the area proportion of the conductive resin in the non-fiber region.

[0057] [Surface resistivity] A test piece of the conductive fiber structure cut to 10 cm x 10 cm was placed on a hard plate-like object with a smooth surface, such as a glass plate, and the surface resistivity (Ω / □) was measured in an environment of 20°C and 40% RH using a low resistivity meter (Mitsubishi Chemical Analytech Corporation, four-point probe resistivity meter "Loresta-AX MCP-T370" and probe "ESP Probe MCP-TP08P").

[0058] [Washing durability] The conductive fiber structure was cut into a test piece of 10 cm x 10 cm, and the surface resistivity after washing 100 times was measured according to the method in accordance with JIS L 0217 (2012) 103. A fully automatic washing machine (TOSHIBA AW-6D6) was used.

[0059] [Example 1] Polyethylene terephthalate containing 2.5 wt% titanium oxide produced by a conventional method and having [η] = 0.657 was melt spun at a spinning speed of 3700 m / min to obtain a 70 dtex 48 filament cross-section POY raw yarn having four recesses. Next, this POY raw yarn was subjected to normal false twisting at a false twist ratio of 1.32 times and a heater temperature of 185°C to obtain a 56 dtex 48 filament false twist textured yarn. A mesh structure knitted fabric was produced using this yarn and a 22 dtex monofilament polyurethane elastic yarn (manufactured by Asahi Kasei Co., Ltd.) on the front side and a SD33 dtex 12 filament polyester circular cross-section false twist textured yarn (manufactured by Nan-A Co., Ltd.) on the back side, and then dyed by a conventional dyeing method to obtain a bare mesh fabric. The content of synthetic fibers with a single fiber fineness of 0.5 to 4 dtex in this fabric was 93% by mass. This bare mesh fabric was used as a substrate, and a conductive resin-forming solution was made by mixing a PEDOT monomer solution (Heraeus CleviosM-V2), an oxidizer and dopant pTS iron salt (Heraeus CleviosC-B40V2), and a solvent ethanol, and then uniformly applied to the top of the substrate in a coating process, and the conductive resin-forming solution was permeated into the inside of the fiber bundle in a permeation process. After that, it was heated at 55°C for 12 minutes, and then kept in a thermostatic chamber at 25°C and 60% humidity for 1 hour to polymerize the PEDOT monomer. The ratio of pTS iron salt to PEDOT monomer was 40:2 by volume, and the ratio of the oxidizer (pTS iron salt) to the total of ethanol and oxidizer (pTS iron salt) was 30% by mass. The amount of application was 1g / 20cm, which is the maximum amount at which droplets do not fall from the fabric. 2 In this way, polymerization was carried out in the state where the resin had penetrated into the substrate, PEDOT was synthesized, and a conductive resin was formed on the fiber surface and within the fiber bundle spaces, resulting in a conductive fiber structure that had been applied in one coat. Next, the maximum amount of liquid that does not fall off the substrate in one application is 1g / 20cm 2 Therefore, in order to incorporate a sufficient amount of conductive resin into the substrate, the conductive fiber structure after the first coating was used as an additional substrate, and a second and third coating, penetration and polymerization were performed in the same manner as above to obtain a three-coated conductive fiber structure. The cross section of the obtained conductive fiber structure was cut, stained with osmium, and observed. The conductive resin had a sponge-like structure with interconnected pores in which granular particles were layered (Fig. 1). The area ratio of the fiber region to the non-fiber region in the obtained conductive fiber structure within a circle of 30 μm diameter containing the four centers of gravity of the cross section of the single fiber was in the range of 55 / 45. The area ratio and area percentage of the conductive resin in the non-fiber region was 65%. These area ratios and area percentages were calculated by observing the cross section of the fiber bundle used for the surface. The surface resistivity of the conductive fiber structure was 5 Ω / □. After the conductive fiber structure was washed 100 times in succession, the surface resistivity was measured in the same way, and it showed a low surface resistivity of 74 Ω / □ even after washing.

[0060] [Example 2] Polyethylene terephthalate containing 2.5 wt% titanium oxide produced by a conventional method and having [η] = 0.657 was melt spun at a spinning speed of 3750 m / min to obtain a 110 dtex 48 filament cross-section POY raw yarn having four recesses. Next, this POY raw yarn was subjected to normal false twisting at a false twist ratio of 1.34 times and a heater temperature of 180°C to obtain a 1-heater false twist textured yarn of 88 dtex 48 filaments. The yarn was subjected to twisting in the S direction at 200 t / m as the warp yarn, and a warp double weave was woven using a polyester circular cross-section 1-heater false twist textured yarn two-ply yarn (manufactured by Kuraray Trading Co., Ltd.) of FD84 dtex 24 filaments (manufactured by Kuraray Trading Co., Ltd.) that was subjected to twisting in the S direction at 300 t / m as the weft yarn. Next, a woven fabric was obtained by dyeing using a conventional dyeing method. The content of synthetic fibers with a single fiber fineness of 0.5 to 4 dtex in this woven fabric was 100% by mass. The application amount was 0.8g / 20cm, the maximum amount at which droplets would not fall off the fabric. 2 The ratio was set at . When this fabric is used as the substrate, the maximum amount of liquid that does not fall off the substrate after one application is 0.8g / 20cm 2 Therefore, in order to incorporate a sufficient amount of conductive resin into the substrate, the amount of conductive resin forming solution applied per application was set to 0.8 g / 20 cm, which is the maximum absorption amount of the fabric. 2 As a result, a series of steps of coating, penetration and polymerization was carried out three times in the same manner as in Example 1 to obtain a conductive fiber structure that had been coated three times. The cross section of the obtained conductive fiber structure was cut, stained with osmium, and observed. The conductive resin had a boundary membrane-like structure that had been peeled off from the synthetic fiber, forming a branched plate-like shape (Fig. 2). The area ratio of the fiber region to the non-fiber region in the obtained conductive fiber structure within a circle of 30 μm in diameter containing the four centers of gravity of the single fiber cross section was in the range of 72 / 28. The area ratio and area percentage of the conductive resin in the non-fiber region were 57%. These area ratios and area percentages were calculated by observing the cross section of the fiber bundle used for the warp thread. The surface resistivity of the conductive fiber structure was 3 Ω / □. After the conductive fiber structure was washed 100 times in succession, the surface resistivity was measured in the same way, and it showed a low surface resistivity of 16 Ω / □ even after washing.

[0061] [Example 3] Polyethylene terephthalate (ETA) of 0.676 containing 0.4 wt% titanium oxide produced by a conventional method was melt spun by a spinning direct drawing method to obtain a 33 dtex 18 filament high shrinkage round cross section drawn yarn with a boiling water shrinkage of 15%. The same resin was also used for high speed spinning at a spinning speed of 4800 m / min to obtain a 33 dtex 18 filament low shrinkage triangular cross section yarn with three recesses and a boiling water shrinkage of 3.2%. Next, both yarns were air entangled using an interlace nozzle to obtain a 66 dtex 36 filament mixed yarn with different shrinkage. The warp yarn was twisted at 1800 t / m in the S direction, and the weft yarn was a 110 dtex 72 filament drawn yarn with a boiling water shrinkage of 7% that was also spinning direct drawing and twisted at 2500 t / m in the S and Z directions, and a satin weave was produced using this yarn. This grey fabric was dyed and relaxed to increase the shrinkage difference, to obtain a mixed fiber satin fabric with different shrinkage rates. The synthetic fiber content of this fabric with a single fiber fineness of 0.5 to 4 dtex was 100% by mass. When this fabric is used as the substrate, the maximum amount of liquid that does not fall off the substrate after one application is 0.6g / 20cm 2 Therefore, in order to incorporate a sufficient amount of conductive resin into the substrate, the amount of conductive resin forming solution applied per application was set to 0.6 g / 20 cm, which is the maximum absorption amount of the fabric. 2 As a result, the same series of steps of coating, penetration and polymerization as in Example 1 were carried out three times to obtain a conductive fiber structure that was coated three times. The cross section of the obtained conductive fiber structure was cut, stained with osmium, and observed. The conductive resin was found to have a thin film or plate-like structure attached to the fibers and between the fibers, and some of it had a sponge-like structure (Fig. 3). The area ratio of the fiber region to the non-fiber region in the obtained conductive fiber structure within a circle with a diameter of 30 μm that contains the four centers of gravity of the single fiber cross section was in the range of 75 / 25. The area ratio and area percentage of the conductive resin in the non-fiber region was 68%. These area ratios and area percentages were calculated by observing the cross section of the fiber bundle used for the warp thread. The surface resistivity of the conductive fiber structure was 7 Ω / □. After washing the conductive fiber structure 100 times in succession, the surface resistivity was measured in the same way, and it was 326 Ω / □, which was an increase in the surface resistivity after washing, but was within the acceptable range.

[0062] [Comparative Example 1] Polyethylene terephthalate containing 2.0 wt% titanium oxide produced by a conventional method and having an [η] of 0.674 was melt spun using a direct spinning drawing method to obtain a normal shrinkage round cross-section drawn yarn of 84 dtex and 72 filaments with a boiling water shrinkage of 7%. A taffeta greige was produced using this yarn as the warp and weft without twist. This greige was dyed by a conventional dyeing method to obtain a taffeta fabric. The content of synthetic fibers with a single fiber fineness of 0.5 to 4 dtex in this fabric was 100% by mass. When this fabric is used as the substrate, the maximum amount of liquid that does not fall off the substrate after one application is 0.4g / 20cm 2 The conductive resin content was insufficient for penetration, but the amount of conductive resin solution applied per application was set to 0.4 g / 20 cm, which is the maximum absorption amount of the fabric. 2 As a result, the same series of steps of coating, penetration and polymerization as in Example 1 were carried out three times to obtain a conductive fiber structure that was coated three times. The cross section of the obtained conductive fiber structure was cut, stained with osmium, and observed. It was found that there were areas where the conductive resin was almost absent and areas where the conductive resin had a sponge-like structure. The area ratio of the fiber area to the non-fiber area in the obtained conductive fiber structure within a circle with a diameter of 30 μm that contains the four centers of gravity of the single fiber cross section was in the range of 70 / 30. The area ratio of the conductive resin in the non-fiber area was 35%. The surface resistivity of the conductive fiber structure was 16 Ω / □. After washing the conductive fiber structure 100 times in succession, the surface resistivity was measured in the same way, but it was not measurable and the conductive resin had almost fallen off after washing, losing conductivity.

[0063] [Table 1]

[0064] As shown in Table 1, the conductive fiber structures of Examples 1 to 3 have a specific fiber region / non-textile region area ratio and a specific conductive resin area ratio in the non-textile region, so that the conductive resin is retained inside the fiber bundles and the conductivity is maintained even after 100 washes, which is the practical value. The conductive fiber structures of Examples 1 and 2 were particularly excellent in washing durability.

[0065] On the other hand, in Comparative Example 1, the area ratio of the conductive resin in the non-textile region was not within a specific range, so that most of the conductive resin fell off after 100 washings, and the washing durability was poor. [Industrial Applicability]

[0066] The conductive fiber structure of the present invention can be used as a bioelectrode for detecting electrical signals from a living body, such as heartbeat, or a bioelectrode for applying electrical stimulation to a living body, such as electrical muscle stimulation (EMS). Such a bioelectrode has a good fit to the living body due to its fiber structure, making it suitable for use as a material that comes into direct contact with the living body, and has excellent washing durability, so can be used as at least a part of various clothing items, such as underwear, footwear, headbands, wristbands, neck wraps, belly wraps, hats, suspenders, gloves, watches, supports, masks, bandages, etc., in addition to pads, gloves, belts, etc.

[0067] As described above, the preferred embodiments of the present invention have been described. However, various additions, modifications, and omissions can be made without departing from the spirit of the present invention, and such additions, modifications, and omissions are also included within the scope of the present invention.

Claims

1. A conductive fiber structure comprising a substrate made of a fiber bundle containing synthetic fibers and a conductive resin present in the substrate, The fiber bundle is composed of a fiber region where fibers are present and a non-fiber region where fibers are not present, In a fiber bundle, a cross section of the fiber bundle cut in a direction perpendicular to the longitudinal direction of the fibers has an area ratio of fiber region / non-fiber region within a circle having a diameter of 30 μm that contains four or more centers of gravity of single fiber cross sections of 20 / 80 to 80 / 20, and the non-fiber region has an area ratio of conductive resin of 40 to 90% in the non-fiber region, and the conductive resin contains a conductive polymer, A conductive fiber structure, wherein the ratio of the total fineness of fibers having a non-circular cross section having three or more recesses to the total fineness of all fibers in the fiber bundle is 50% or more.

2. 2. The conductive fiber structure according to claim 1, wherein the conductive resin is present between the separated monofilaments in the form of a sponge and / or a boundary film having interconnected pores.

3. 3. The conductive fiber structure according to claim 1 or 2, wherein the substrate comprises synthetic fibers having a single fiber fineness of 0.5 to 4 dtex.

4. A conductive fiber structure as described in claim 3, wherein synthetic fibers having a single fiber fineness of 0.5 to 4 dtex account for 40 mass% or more of the fibers constituting the substrate.

5. 5. The conductive fiber structure according to claim 1, wherein the surface resistivity after 100 washings is 200 Ω / □ or less.

6. A bioelectrode comprising the conductive fiber structure according to any one of claims 1 to 5 as an electrode.

Citation Information

Patent Citations

  • Super-hydrophobic washable conductive fabric and preparation method thereof

    CN102619093A

  • Charge indicator

    JP1982006539A

  • Magnetic card reader / writer device

    JP1989076480A

  • Production of electrically conductive yarn

    JP1989266280A

  • Conductive adhesive sheet

    JP1994104093A